PENGARUH KOMBINASI PAKAN ALAMI (DAUN PEPAYA- KUNYIT- DAUN SINGKONG-BEKATUL) TERHADAP PERTUMBUHAN KELINCI NEW ZEALAND WHITE (Lepus negricollis) SEBAGAI SUMBER BELAJAR - Febri Hartono; HRA Mulyani; Suharno Zen (EDUBIOLOCK, 2023)
New Zealand White Rabbit (Lepus negricollis) is a good growth by requiring good nutrition for growth. Combination of natural food (Papaya Leaf-Turmeric-Cassava Leaf-Bekatul) as an alternative for rabbit feed. This study aims (1) to determine the effect of a combination of natural food (Papaya-Turmeric-Cassava Leaf-Bekatul) on the growth of New Zealand White (NZW) rabbits (Lepus negricollis), (2) to determine the best combination for New Zealand White (NZW)rabbit (Lepus negricollis)growth, (3) To find out whether the results of this study can be used as a biology learning of source in growth and development material in the form of Student Worksheets(SW). The research was carried out for 30 days, rabbits were given feed at 06:00 AM and 07:00 PM. The results showed that there was an effect of eating a combination of natural foods on the growth of rabbits. The best growth in weight and length was in the P3 treatment with a combination of papaya leaves, turmeric, cassava leaves, rice bran as much as 35% with a long growth yield of 6.75 cm and a weight of 390gr. The results of this study can be used as a learning resource for high school biology class XII in the form of Student Worksheets (SW) for growth material and living things.